2006
DOI: 10.1614/ws-05-54.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on slender amaranth (Amaranthus viridis) germination

Abstract: Germination response of slender amaranth to temperature, solution pH, moisture stress, and depth of emergence was evaluated under controlled environmental conditions. Results indicated that 30 C was the optimum constant temperature for germination. Germination of slender amaranth seed at 21 d was similar, with 35/25, 35/20, 30/25, and 30/20 alternating temperature regimes. As temperatures in alternating regimes increased, time to onset of germination decreased and rate of germination increased. Slender amarant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 21 publications
7
34
0
2
Order By: Relevance
“…Similar germination response of A . viridis to water stress was also demonstrated in the study of Thomas et al [31]. In their study, extremely low germination (1.25% at 30/20°C) at -0.4MPa was reported which was the lethal osmotic potential causing complete inhibition in our study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar germination response of A . viridis to water stress was also demonstrated in the study of Thomas et al [31]. In their study, extremely low germination (1.25% at 30/20°C) at -0.4MPa was reported which was the lethal osmotic potential causing complete inhibition in our study.…”
Section: Discussionsupporting
confidence: 87%
“…spinosus [32], and A . viridis [31], [32]. In a study by Ghorbani et al [26], the germination of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe et al (2002) reported similar behavior for invasive weed species. Seed germination of many weed species remained unaffected (from pH 4 to 9) in various studies (Thomas et al, 2006;Chachalis et al, 2008;Wang et al, 2009). Germination of coolatai grass was 92% at pH level of 7.00, however at moderate level of pH (5.00) or (9.00) germination was reduced by around 10%.…”
Section: Effect Of Phmentioning
confidence: 99%
“…However, reasonable emergence of A. tenuifolius also occurred at 1, 2 and 3 cm burial depths. Studies by Thomas et al (2006) showed that seeds of Amaranthus viridis (Slender Amaranth) emerged in between 0.5 and 2 cm. Contrary to the above findings, the emergence of threehorn bedstraw was negligible at soil surface and it increased with increasing burial depths up to 5 cm (Chauhan et al, 2006d).…”
Section: Effect Of Seeding Depthmentioning
confidence: 99%